Analysis of Time and Cost Control Using The Earned Value Method In Well Pad Hilling and Compacting Work In The PT. Pertamina Hulu Rokan Riau Province - Bonny, Apde; Oetomo, Wateno; Marleno, Risma (Devotion : Journal of Research and Community Service, 2022)
The development of physical facilities in Indonesia is increasing rapidly along with the promotion of modernization. In the implementation of a project it is very rare to find a project that goes exactly as planned. Generally, they experience delays from what was planned, both in terms of time and progress of work, but there are also projects that experience acceleration from the initial schedule planned. The research objectives were to determine time and cost performance, and to determine cost estimates and final project completion time for the Well Pad stockpiling and compaction project in the Rokan Riau Oil and Gas Block environment. The method used in this study is the Earned Value method which combines the elements of cost and time as well as the physical performance of the work. The data obtained from the project includes the project time schedule, budget plan (RAB), project weekly reports and actual costs, then an analysis of costs, schedules, variances and performance indexes is carried out by explaining the problems that arise during the research. Based on the results of the analysis and discussion, the calculation of the CPI value is> 1 from the 1st week to the 16th week. This means that from the 1st week to the 16th week, the project cost is more economical. The EAS calculation for the 16th week estimates the project completion time is 116 days or 16 weeks. This means that the project is experiencing a delay from the planned schedule. At the end of the review period, an estimated final project cost of Rp. 4,022,024,000.00. And the estimated time for project completion is 116 days, which means the project will be completed in a longer time than planned, which is 211 days.